Peran Hukum Adat dalam Pelestarian Tradisi Suku Baduy di Banten - Purwanti (Universitas Ngudi Waluyo, 2025)
This study examines the vital role of the customary law of the Baduy Tribe in efforts to preserve their traditions and natural order. The Baduy customary law is deeply rooted in the Sunda Wiwitan belief and the principle of